2022
DOI: 10.1038/s41467-022-31158-x
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the phase transition-induced ultrahigh piezoresponse in (K,Na)NbO3-based piezoceramics

Abstract: Here, we introduce phase change mechanisms in lead-free piezoceramics as a strategy to utilize attendant volume change for harvesting large electrostrain. In the newly developed (K,Na)NbO3 solid-solution at the polymorphic phase boundary we combine atomic mapping of the local polar vector with in situ synchrotron X-ray diffraction and density functional theory to uncover the phase change and interpret its underlying nature. We demonstrate that an electric field-induced phase transition between orthorhombic and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 63 publications
(32 citation statements)
references
References 76 publications
1
31
0
Order By: Relevance
“…The application of a low DC bias eld does not substantially impact the dimension of the crystalline region and the crystal structure of the P(VDF-TrFE) 18,31 . As shown in Fig.…”
Section: Induced Piezoelectricity In Unpoled Ferroelectric Polymer P(...mentioning
confidence: 99%
“…The application of a low DC bias eld does not substantially impact the dimension of the crystalline region and the crystal structure of the P(VDF-TrFE) 18,31 . As shown in Fig.…”
Section: Induced Piezoelectricity In Unpoled Ferroelectric Polymer P(...mentioning
confidence: 99%
“…In addition, due to the toxicity of Pb, environmentally benign lead-free piezoelectrics have received intensive attention, such as BaTiO 3 [ 39 , 40 , 41 ], sodium bismuth titanate (BNT) [ 42 , 43 , 44 ], and potassium sodium niobate (KNN) [ 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ]. In Figure 2 b, Jong et al demonstrated a BaTiO 3 hybrid film by adopting a simple and facile inkjet-printing process [ 53 ].…”
Section: Piezoelectric Materialsmentioning
confidence: 99%
“…For O-phase KNN, increased temperature can increase the dipole activity and enhance the ε r , but at the same time, it can also decrease the d 33 because of the reduction in the asymmetry of the system. 13 Because the non-synergistic change in the two parameters leads to temperature sensitivity of the FOM, it cannot be used in PEHs with stable working requirements.…”
Section: Introductionmentioning
confidence: 99%